A Comparative Study of Technology Approaches in Using Online Marketing Strategies for Small and Medium Enterprises in Indonesia During the COVID-19 PANDEMIC (Universitas Ahmad Dahlan, 2022)
The impact of the coronavirus pandemic has been felt in the business and financial world. In a fairly short time, marketing patterns have changed, especially when social distancing is enforced and micro-restrictions. Business actors have to rack their brains to be able to market their products or services to consumers as a brand strategy to survive amid the coronavirus pandemic. Business people optimize online marketing and digital branding to communicate with their target consumers. The COVID-19 PANDEMIC has also accelerated digitalization in the marketing sector. Online sales are one of the solutions to the limited physical movement of people to visit shopping centres. The switch to online marketing is also one strategy that determines whether or not a product can survive during a pandemic. This study describes how small and Medium Enterprises in Indonesia face the Covid 19 pandemic. It is hoped that this literature study can provide an overview of the condition of MSMEs in Indonesia during the pandemic to improve welfare through online marketing.